The novelty of newspapers Victorian fiction after the invention of the news - Rubery, Matthew (Oxford University Press, 2009)
Focusing on five diverse narrative conventions: the shipping intelligence, personal advertisement, leading article, interview, and foreign correspondence, this work shows journalism's concrete influence on the novel in the Victorian era.